Craving and subsequent opioid use among opioid dependent patients who initiate treatment with buprenorphine - Tsui, Judith I. (Am J Drug Alcohol Abuse, 2014)
BACKGROUND: Few studies have directly assessed associations between craving and subsequent opioid use among treated patients. Our objective was to prospectively evaluate the relative utility of two craving questionnaires to predict opioid use among opioid dependent patients in treatment. METHOD: Opioid dependent patients (n=147) initiating buprenorphine treatment were assessed for three months. Craving was measured using: 1) the Desires for Drug Questionnaire (DDQ) and 2) the Penn Alcohol-Craving Scale adapted for opioid craving (PCS) for this study. Multi-level logistic regression models estimated the effects of craving on the likelihood of opioid use after adjusting for gender, age, ethnicity, education, opioid of choice, frequency of use, pain and depression. In these analyses craving assessed at time t was entered as a time-varying predictor of opioid use at time t+1. RESULTS: In adjusted regression models, a 1-point increase in PCS scores (on a 7-point scale) was associated with a significant increase in the odds of opioid use at the subsequent assessment (OR = 1.27, 95% CI 1.08; 1.49, p < .01). The odds of opioid use at the subsequent follow-up assessment increased significantly as DDQ desire and intention scores increased (OR = 1.25, 95%CI 1.03; 1.51, p< .05), but was not associated significantly with DDQ negative reinforcement (OR = 1.01, 95%CI 0.88; 1.17, p > .05) or DDQ control (OR = 0.97, 95%CI 0.85; 1.11, p > .05) scores. CONCLUSION: Self-reported craving for opioids was associated with subsequent lapse to opioid use among a cohort of patients treated with buprenorphine.